Moving Towards Secure Flexibility – Development of the Social Dimension of the European Union - Jakab, Nóra (Maastricht 30: A Central European Perspective, 2025)
Access to decent working conditions and social protection is crucial for the economic and social security of the workforce and for well-functioning labour markets that create jobs and sustainable growth. At the same time, there is a growing number of people who do not have sufficient access to labour and social protection due to the type of employment or self-employment. In the development of the social dimension of the European Union, I consider the pursuit of employment security for workers in the labour market to be a major achievement. What does employment security mean? Who are the workers who need protection? These are the two fundamental questions of this study, which, since the adoption of the Maastricht Treaty, have lent a new dimension to our views on security and flexibility. I am convinced that we are no longer talking about flexicurity but about secure flexibility. At least, this is whatthe European Commission’s efforts, the case law of the European Court of Justice and individual (Member) State decisions on employment status are leading us to believe.Keywords: fair working conditions, information directive, minimum rights, labour and social law protection, social dimension, secure flexibility